Taxation and capital structure choice: evidence from a panel of German multinationals - Thiess Büttner; Michael Overesch; Ulrich Schreiber; Georg Wamser (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
This paper analyzes the impact of taxes and lending conditions on the financial structure of multinationals? foreign affiliates. The empirical analysis employs a large panel of affiliates of German multinationals in 26 countries in the period from 1996 until 2003. In accordance with the theoretical predictions, the effect of local taxes on leverage is positive for both types of debt. Moreover, while adverse local credit market conditions are found to reduce external borrowing, internal debt is increasing, supporting the view that the two channels of debt finance are substitutes.
Keywords: H25; G32; H26; 330; Corporate Income Tax; Multinationals; Capital Structure; Firm-Level Data